STATUS AND TRENDS OF CHANGE IN DISTRIBUTION OF MARINE HABITATS IN NHA TRANG BAY - Long, Nguyen Van; Son, Tong Phuoc Hoang (Vietnam Journal of Marine Science and Technology, 2018)
Assessments of status and temporal changes in distribution of marine habitats in Nha Trang bay were conducted by using interpretation of remote sensing (Orbview 3, SPOT5, ALOS-AVNIR2 and Landsat 8-LCM) and aerial images in combination with ground truthing at 50 key sites representing coral reefs (25 sites), seagrass beds (10 sites), mangroves (5 sites), rocks (5 sites) and sand (5 sites) in 2015. A total of 812 ha of key marine habitats was recorded in 2015 including 754.1 ha of coral reefs, 52.4 ha of seagrass beds and 5.4 ha of mangroves. There was a notable decline in areas of the above marine habitats in the period of 2002 - 2015, in which 64 ha of seagrass beds (equivalent to 45%; mainly at Bai Tien, Phu Quy, Mui Nam and Vung Me, Đam Gia, Song Lo) and 117.4 ha of coral reefs (equivalent to 13.5%; mainly at Dam Gia, Duong De, Song Lo, Bai Tien and Eo Co) have been lost with an exception of increase of 3.1 ha of mangroves by new transplantation project conducted by Nha Trang MPA authority in Dam Bay during the last few years. The decline in the areas of coral reefs and seagrass beds has been caused by expansion and reclaimation of infrastructure for community and tourism development in recent years